2012
DOI: 10.4317/medoral.17336
|View full text |Cite
|
Sign up to set email alerts
|

Double-application of platelet-rich plasma on bone healing in rabbits

Abstract: Objective: Platelet-rich plasma (PRP) is considered to enhance bone formation especially at early stages of wound healing, depending on the limited and short life-span of platelets and growth factors. The aim of this study was to evaluate efficacy of double-application of PRP (DA-PRP) on bone healing in a rabbit calvarial defect model. Study design: Twenty-eight rabbits, each had two surgically prepared calvarial bone defects (10mm diameter), were included in this study and randomly divided into six groups. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
(51 reference statements)
1
11
0
1
Order By: Relevance
“…Upper yellow layer consisted of platelet-rich and platelet-poor plasma, while lower red layer consisted of erythrocytes and leukocytes, as has previously been documented. [30] Lower red layer has been reported to be rich in platelets that recently entered the circulation. [31,32] Total plasma consisting of complete upper yellow layer and top 1 to 2 mm of lower red layer was transferred to sterile monovette.…”
Section: Allogeneic Prp Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper yellow layer consisted of platelet-rich and platelet-poor plasma, while lower red layer consisted of erythrocytes and leukocytes, as has previously been documented. [30] Lower red layer has been reported to be rich in platelets that recently entered the circulation. [31,32] Total plasma consisting of complete upper yellow layer and top 1 to 2 mm of lower red layer was transferred to sterile monovette.…”
Section: Allogeneic Prp Preparationmentioning
confidence: 99%
“…After second centrifugation at 4000 rpm for 7 minutes, approximately 0.7 mm at the bottom of the monovette was platelet-rich plasma and upper portion was mostly platelet-poor plasma. [30] Supernatant platelet-poor plasma was collected and removed by pipette. Remaining platelet-rich plasma was then carefully transferred into application injector.…”
Section: Allogeneic Prp Preparationmentioning
confidence: 99%
“…It is commercially available as blocks or granules. There are several papers combining TCP to GF, with positive and negative results 40,44 . Afifi et al 45 have demonstrated that TCP alone has a non-negligible tax of complications in cranioplasties, especially when inserted in previously irradiated areas, or for those in contact with paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the experimental ( 7 , 8 , 10 ) and clinical ( 1 , 5 , 6 ) studies which examine the effects of PRP on the healing of bony defects, have focused on the single-application of PRP to the wound area. Recently, promising results on soft tissue healing have been suggested by multiple-application of PRP ( 11 , 12 , 13 , 14 , 15 ). Crovetti et al ( 11 ) reported that following topical treatment with multi-application of PRP, 9 out of 24 cutaneous chronic nonresponsive severe ulcers healed completely and eight healed by more than 50%.…”
Section: Introductionmentioning
confidence: 99%